SOME OBSERVATIONS ON ACCOUNTING IN FRANCE AND GERMANY. - Baily, H. H. (The Accounting Review, 1929)
Abstract To get a proper perspective of the development of accounting in any country one must understand the institutions, the characteristics of the people, and the peculiarities of their business practice. In France and Germany as in other European countries they have many hundreds of years behind them. Their institutions are the result of growth through many generations. Society in the United States is not as static and there is more freedom of movement between people in different walks of life. The French business man does not have the proper attitude towards the accountant. The accountant is a necessary evil. The accounting department is regarded as an expense rather than as a part of the organization that aids in the development of efficiency and as an important factor in the success of any large business. Without doubt French law has had some influence on the development of accounting in France. The French accountants have not organized themselves into strong professional societies. Instead of a few strong organizations they have many loosely joined.